Evaluation of novel hydrogen integration options in bio-oils introduction to petrochemical refineries. (1st September 2022) - Bampaou, M.; Panopoulos, K.D.; Seferlis, P.; Voutetakis, S.
Abstract: Biomass integration into refineries allows to utilize existing infrastructures without deviating from established production routes and partially substitute fossil-with renewable-carbon. In particular, biomass after being converted by pyrolysis into bio-oil and then upgraded in the hydrotreatment section, it is inserted into existing refinery operations. Hydrogen is a key component during hydroprocessing since it is renewable and used in high excess. Reusing that unreacted hydrogen could prove beneficial for the economic viability of this scheme. An alternative hydrogen recovery technology is electrochemical compression that has the ability to recover and simultaneously compress hydrogen. The proposed biorefinery concept consists of the following subsystems: pyrolysis, hydrotreatment, gas cleaning, electrochemical hydrogen compression and PEM electrolysis. This work investigates the proposed scheme through flowsheet simulations and by determining crucial operating parameters that affect the overall economic and energetic performance. Results showed that recycling using an electrochemical compressor has significant economic and energetic benefits. Substantial cost reductions can also be attained from the economies-of-scale and by utilizing inexpensive electricity and biomass feedstocks. Overall, although the renewable hydrogen production cost surpasses that of the fossil-based, progress in the hydrogen processing techniques can further lower the expenses, transforming renewable hydrogen into a vital component for existing technologies. Highlights: A pyrolysis-based biorefinery integrating renewable hydrogen is investigated. Electrochemical hydrogen compression is employed for hydrogen recycling. Potential co-processing options of bio-oils in the refinery are reviewed. Crucial operating parameters are investigated. The proposed biorefinery scheme is economically assessed.